2019
DOI: 10.7759/cureus.5422
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Between the European Organization for Research and Treatment of Cancer and Positron Emission Tomography Response Criteria in Solid Tumors in Evaluating Treatment Response in Solid Malignant Tumors

Abstract: IntroductionFluorine-18 fluorodeoxyglucose (FDG) positron emission tomography-computed tomography (PET-CT) is used for non-invasive staging and restaging of solid malignant tumors. PET-CT based criteria have been developed to evaluate the response to targeted therapy. These include the European Organization for Research and Treatment of Cancer (EORTC) and the PET Response Criteria in Solid Tumors (PERCIST). The aim of this study was to determine the agreement between EORTC and PERCIST criteria for treatment re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…One patient with SMD by PERCIST was categorized as PMD by EORTC. Nasir et al [ 23 ] reported that the agreement between EORTC and PERCIST criteria for treatment response evaluation in patients with solid malignant tumors. The same authors mentioned that adoption of EORTC or PERCIST in 18 F-FDG PET/CT reports can standardize the evaluation of oncological treatment results.…”
Section: Discussionmentioning
confidence: 99%
“…One patient with SMD by PERCIST was categorized as PMD by EORTC. Nasir et al [ 23 ] reported that the agreement between EORTC and PERCIST criteria for treatment response evaluation in patients with solid malignant tumors. The same authors mentioned that adoption of EORTC or PERCIST in 18 F-FDG PET/CT reports can standardize the evaluation of oncological treatment results.…”
Section: Discussionmentioning
confidence: 99%